Estudo molecular do tumor odontogênico queratocístico e do cisto odontogênico ortoqueratinizado - Marina Goncalves Diniz (2012)
The odontogenic keratocyst, or odontogenic keratocyst tumor (TOQ), and the odontogenic cyst orthokeratinized (COO) are distinct histologic types of odontogenic cyst presenting histological similarities, however, biological and clinical differences. Mutation and loss of heterozygosity in the tumor suppressor gene Patched 1 (PTCH) have been demonstrated in TOQ plus high expression of the anti-apoptotic gene B-cell CLL/lymphoma 2 (BCL2) compared to the COO and other odontogenic cysts. The PTCH protein is involved in the Hedgehog pathway (via HH) by suppressing the expression of several target genes important for development. The gene BCL2 encodes a protein capable of stopping apoptosis, facilitating survival of the cell independent of promoting cell division. Among the mechanisms that can lead to increased expression of BCL2 is the loss of microRNAs (miRNAs) miR15a/16-1. In this study we set out to investigate the molecular aspects of TOQ and COO in an attempt to discover probable pathogenic mechanisms that explain the histopathological similarities between TOQ and COO and clinical aggressiveness and great tendency to recurrence of the former. Therefore, we evaluated the allelic loss (PA) of the region associated with the PTCH gene, 9q22.3-31, in COO and TOQ and investigated the expression of miRNAs miR-15a and miR-16-1 and its impact on the expression of BCL2 in TOQ. The microsatellites markers D9S287, D9S196, and D9S127 were investigated for PA. There was loss in at least one locus in 5 7 TOQ and in 4 7 COO samples. By using real time PCR (qRT-PCR), we found miR-15a and/or miR-16-1 downregulation in the majority of TOQ samples (24/28). We also found higher BCL2 mRNA expression in 19 out of 20 TOQ frozen samples through qRT-PCR. Additionally, moderate to high Bcl-2 imunopositivity was found in the basal layer cells in 16 out of 18 paraffin embedded TOQ (median: 42.6%). In vitro over-expression of miR-15a/16-1 in human TOQ primary cell culture (KCOT-1) resulted in a decrease of Bcl-2 protein expression. Furthermore, all five paired TOQs collected before (primary tumor) and after the marsupialization procedure (marsupialized tumor) exhibited increased levels of miR-15a expression after this surgical procedure (p = 0.04). Our findings demonstrate that, despite the existence of clinical, morphological, immunohistochemical, and biological behavior differences between COO and TOQ, both harbor similar genetic alterations at 9q. Also, our results strongly suggest that TOQ neoplastic cells present an anti-apoptotic profile to which a lower miR-15a/16-1 expression might be related. Additionally, we demonstrated that miRNA expression 17 increases after marsupialization, implicating an etiological and therapeutic role of these small RNA molecules in TOQ.